A concise history of sociology's 'indigenization' in postwar Taiwan: Emergence, transformation, and invisibilization. (September 2021) - Lin, Feng-Tsan; Wu, Huang-Chang; Tang, Chih-Chieh
In Taiwan, sociology is 'the Western knowledge' by its origin, and inevitably will be indigenized, especially in the process of teaching or researching. The development of sociology in postwar Taiwan takes a crooked path. It is in the crooked path to postwar that the indigenization in Taiwan's sociology takes different faces, employing different terminology and constellating around different academic figures to embody the indigenization as we have known today. Although the path from sinicization to Taiwanization may nicely capture the basic line of Taiwan's sociology after the Second World War, it does fail to reveal the details that can suggest to a more dynamic, more controversial side of indigenization. In this short article, we review the emergence, transformation, and invisibilization of indigenization in postwar Taiwan in the following three aspects: its periodization, the socio-political background in which the debate is embedded, and the key issues involved. While the indigenization debate has been subsiding in last decade, we will argue that the ideal which the debate evinces is still significant and influential. In conclusion, we propose an alternative view to rethink the indigenization of Taiwan's sociology. In terms of reciprocal comparison and connected histories, Taiwan's case exemplifies an alternative trajectory of modernity, which is potential to correct the hitherto double historical misrecognition of modernity upheld by classical sociological theories, and to build a new synthesis or a new theory of modernities.